2009
DOI: 10.1128/jvi.00739-09
|View full text |Cite|
|
Sign up to set email alerts
|

Subcellular Localization of the Barley Stripe Mosaic Virus Triple Gene Block Proteins

Abstract: We have now used Agrobacterium tumefaciens-mediated protein expression in Nicotiana benthamiana leaf cells and site-specific mutagenesis to determine how TGB protein interactions influence their subcellular localization and virus spread. Confocal microscopy revealed that the TGB3 protein localizes at the cell wall (CW) in close association with plasmodesmata and that the deletion or mutagenesis of a single amino acid at the immediate C terminus can affect CW targeting. TGB3 also directed the localization of TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 60 publications
5
72
0
Order By: Relevance
“…All mutated sequences were verified by sequencing. Abaxial infiltrations of N. benthamiana leaves with Agrobacterium tumefaciens were performed essentially as described previously (Lim et al, 2009), applying a final concentration of 0.6 OD 600 , with constructs mixed in equal proportions where appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mutated sequences were verified by sequencing. Abaxial infiltrations of N. benthamiana leaves with Agrobacterium tumefaciens were performed essentially as described previously (Lim et al, 2009), applying a final concentration of 0.6 OD 600 , with constructs mixed in equal proportions where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular localization of several class I (hordeivirus-like) and class II (potexvirus-like) TGB proteins has been investigated by using fluorescent gene fusions (Haupt et al, 2005;Ju et al, 2005;Lim et al, 2009;Lough et al, 1998;Solovyev et al, 2000). To assess localization of AltMV TGB3, we expressed TGB3 from pGDR and pGDG (Goodin et al, 2002) or pHVLR and pHVLG vectors for Agrobacteriummediated transient expression of DsRed or green fluorescent protein (GFP) fusions (Fig.…”
Section: Subcellular Localization Of Pvx and Altmv Tgb3mentioning
confidence: 99%
“…These roles of TGBp3 and TGBp2 are consistent with their ability to increase the size exclusion limit of plasmodesmata (23). Yeast two-hybrid assays have shown that TGBp3 and TGBp2 self-interact and interact with each other (24,25), which is important for TGB functions, because disruption of the TGBp2-TGBp3 interaction inhibits the movement of Barley stripe mosaic virus (BSMV) (genus Hordeivirus) (26,27). Previous studies suggested that TGB proteins must be expressed at suitable relative molarities for viral movement to occur.…”
mentioning
confidence: 72%
“…Previous studies suggested that TGB proteins must be expressed at suitable relative molarities for viral movement to occur. For example, the optimal relative expression ratio of TGBp2 and TGBp3 is 10:1 in BSMV and PMTV (25,28), and TGBp2 and TGBp3 should be expressed at 10-and 100-fold-lower levels, respectively, than TGBp1 (27,29,30). Previous studies on PMTV TGBp3 have been done by producing the protein from a plant expression vector or heterologous virus (e.g., see references [23][24][25].…”
mentioning
confidence: 99%
“…It also serves as a more economically feasible approach compared to instances where in vitro RNA transcription is required for the infection of cells for mechanical inoculation [25]. Even a robust approach like agrobacterium mediated gene transfer doesn't come without limitations, as it is limited to dicotyledonous plants and is not amenable for monocots [26]. Moreover, there is difference in the virulence of strains for Agrobacterium tumefaciens, and requires extensive optimization of technique as a protocol for transformation differs from one species to another [25,27].…”
Section: Life Sciences Researchmentioning
confidence: 99%